Halal Product Standardization in Vietnam: Lessons from Indonesia for Inclusive and Sustainable Development: Standarisasi Produk Halal di Vietnam: Pelajaran dari Indonesia untuk Pembangunan Inklusif dan Berkelanjutan - Andi Setyo Pambudi; Alan Yazid Ali Basjah; Hasan Ashari; Eddy Rusman; Isti Yuli Ismawati; Yudhi Putro (Jurnal Bisnis dan Ekonomi, 2025)
Abstract The global phenomenon of the halal industry demonstrates its evolution from a normative religious issue into a driver of international economic growth with strong implications for social, cultural, and environmental dimensions. Nevertheless, a research gap persists as most academic studies focus on Muslim-majority countries, while the potential of non-Muslim countries such as Vietnam remains underexplored. This study is crucial to address the urgency of developing Vietnam’s halal industry, which has a strong foundation in agriculture, fisheries, coffee, and spices with high export potential. The objectives of this research are to analyze how Vietnam’s halal economy can be optimized through lessons learned from Indonesia, to examine the role of social inclusivity in strengthening cross-cultural cohesion, to understand the integration of halal principles with sustainable development agendas, and to propose an international collaboration model based on co-learning, co-design, and co-invest. The research adopts a qualitative descriptive approach through literature studies, field observations in Ho Chi Minh City, and focused group discussions. The findings reveal that halal functions as a strategic instrument for economic competitiveness, social cohesion, and environmental sustainability. Recommendations include establishing a national halal authority, promoting green halal, and strengthening regional halal diplomacy. This study contributes to enriching the literature on halal development in non-Muslim countries while providing practical policy insights for Vietnam and Indonesia. Keywords: halal, Vietnam, Indonesia, sustainability, international collaboration